1978
DOI: 10.1093/ajcn/31.10.1948
|View full text |Cite
|
Sign up to set email alerts
|

Hypogeusia and zinc depletion in chronic dialysis patients

Abstract: Dialysis patients generally have a poor appetite, do not enjoy eating, and complain of food, particularly protein, as being disagreeable. Twenty dialysis patients with the above symptoms were tested for taste acuity, serum zinc (Zn), Zn concentrations in hair samples (intracellular Zn), and daily caloric intake. A double-blind, cross-over study was instituted using a Zn supplement and a placebo. After supplementation with Zn, taste acuity markedly improved in 95% of patients and Zn concentrations in hair incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(55 citation statements)
references
References 8 publications
5
48
1
1
Order By: Relevance
“…AtkinThortx al. [7] demonstrated an improvement in taste acuity following oral zinc sulfate ther apy in hemodialysis patients with low serum zinc levels. The cause and clinical signifi cance of low serum zinc in hemodialysis pa tients has not yet been established.…”
Section: Introductionmentioning
confidence: 95%
“…AtkinThortx al. [7] demonstrated an improvement in taste acuity following oral zinc sulfate ther apy in hemodialysis patients with low serum zinc levels. The cause and clinical signifi cance of low serum zinc in hemodialysis pa tients has not yet been established.…”
Section: Introductionmentioning
confidence: 95%
“…Patients with CRF have low plasma zinc concentrations [5,6], al though this may not necessarily be indicative of zinc de ficiency. Recently, Atkin-Thor et al [7] and O'Nion et al [8] reported that chronic hemodialysis patients had hypo geusia. associated with low serum, red blood cell, and hair zinc concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The decreased gustin levels may also relate to an inability to absorb, transport, or store zinc. Approximately one-quarter of patients with taste and smell dysfunction have been found to exhibit zinc-malabsorption (31), and patients with chronic renal disease exhibit hypogeusia, hypogonadism, and other signs of zinc deficiency (32)(33)(34)(35)(36)(37)(38), which have been corrected with exogenous zinc therapy in controlled clinical trials (36)(37)(38).…”
Section: Methodsmentioning
confidence: 99%